Study of the fatigue behavior of a synthetic rubber undergoing cumulative damage tests. (October 2016) - Cruanes, C.; Lacroix, F.; Berton, G.; Méo, S.; Ranganathan, N.
Highlights: Fatigue tests alternating damaging and non-damaging force controlled loading are presented. The fatigue life is 5 to 8.4 times higher than during a constant amplitude fatigue test. For each loading, a different behavior between the first and the following blocks has been observed. The evolution of the deformation and the hysteresis area during the blocks is investigated. The global reinforcement seems to be linked to the strain induced crystallization. Abstract: Fatigue damage tests were carried on polychloroprene rubber using a loading sequence with alternate blocks of two force amplitudes, one being damaging and the other not, and carried until the failure of the dumbbell-shaped samples. The duration of the blocks was investigated and chosen to be higher than 20% of the fatigue life of the damaging loading. The presence of cracks was assured by preliminary micro-tomography measurements on samples undergoing constant amplitude fatigue tests at the damaging solicitation. It was observed that the sum of cycles to failure at this damaging loading was more than 5 times the fatigue life at constant amplitude. The behavior of the hysteresis area, the maximal and the minimal strain hinted that the explanation of such an improvement of the fatigue characteristic was caused by the relationship between the crack growth, the strain-induced crystallized area at the tip of those cracks and the self-heating.